2003
DOI: 10.1063/1.1618355
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron emission microscopy observation of inversion domain boundaries of GaN-based lateral polarity heterostructures

Abstract: An intentionally grown GaN film with laterally patterned Ga-and N-face polarities is studied using in situ UV-photoelectron emission microscopy ͑PEEM͒. Before chemical vapor cleaning of the surface, the emission contrast between the Ga-and N-face polarities regions was not significant. However, after cleaning the emission contrast between the different polarity regions was enhanced such that the N-face regions exhibited increased emission over the Ga-face regions. The results indicate that the emission thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 21 publications
4
31
0
3
Order By: Relevance
“…Recently, we demonstrated that PEEM is capable of imaging of Ga-and N-face regions of cleaned GaN films. 9 The contrast was due to the enhanced emission from the N-face regions, which was attributed to the photoemission of electrons in the conduction band at the surface induced by band bending. Similarly, a variation in electron affinity and/or band bending could give rise to ferroelectric domain contrast in PEEM.…”
Section: Polarization-dependent Electron Affinity Of Linbo 3 Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that PEEM is capable of imaging of Ga-and N-face regions of cleaned GaN films. 9 The contrast was due to the enhanced emission from the N-face regions, which was attributed to the photoemission of electrons in the conduction band at the surface induced by band bending. Similarly, a variation in electron affinity and/or band bending could give rise to ferroelectric domain contrast in PEEM.…”
Section: Polarization-dependent Electron Affinity Of Linbo 3 Surfacesmentioning
confidence: 99%
“…13 In contrast, for an actual semiconductor surface, the threshold is dependent on the band structure at the surface, which can vary with the doping and the band bending. 9 It is noted that due to its E g of 3.9 eV, LNO would be considered as a wide band-gap ferroelectric semiconductor. 12 Thus, to understand the origin of the PEEM polarity contrast mechanism of the ferroelectric domains, it is necessary to consider the effects of band bending and electron affinity.…”
Section: Polarization-dependent Electron Affinity Of Linbo 3 Surfacesmentioning
confidence: 99%
“…1 In prior studies from our group, the surfaces of a GaN-lateral polarity heterostructure ͑LPH͒ have been investigated using PFM, Raman scattering and photoelectron emission microscopy ͑PEEM͒. [4][5][6] In this study, SKPM and EFM have been employed to measure the relative surface potentials and surface charge densities of Ga-and N-face GaN. In order to address the role of adsorbed charge in polarization screening on GaN, the measurements are made before and after a wet chemical treatment that modifies the surface in a controlled way.…”
mentioning
confidence: 99%
“…365 nm to 13.6 µm for GaN) over both conventional LiNbO 3 and GaAs QPM structures. It is now possible to produce periodically patterned lateral polarity heterostructures (LPH) [1][2][3]. However, the growth of high quality crystalline Ga-and N-face GaN with small inversion domain boundary regions (IDBR) is still a challenge.…”
mentioning
confidence: 97%
“…The wurtzite III-nitrides (Al x Ga 1-x N) provide distinct advantages such as a wide window of transparency (e.g. 365 nm to 13.6 µm for GaN) over both conventional LiNbO 3 and GaAs QPM structures. It is now possible to produce periodically patterned lateral polarity heterostructures (LPH) [1][2][3].…”
mentioning
confidence: 99%